Eco-friendly produced superfine Moringa oleifera nanometric food powder and its characteristic effect on its structural, morphological and toxicity for varied applications as new functional nanomaterials. (2023) - Kumar Naik, Naman; Kr Singh, Rakesh; Singh, Pallavi; Kumar, Nishant; Ahmed, Ghufran; Narayan, Shyam
Abstract: The present study investigates the characteristic changes brought in the structural and morphological properties of the Moringa oleifera leaf superfine nanoscale powder synthesized via High Energy Ball Milling machine and characterized by employing modern scientific tools. Moringa oleifera leaves were procured locally. The leaves were thoroughly washed with DI water to remove any contaminants followed by drying in laboratory using micro-wave oven at 50°C. The dried leaves were then ground coarsely in the mixer grinder for 10 min. Part of the coarsely ground powder was labelled as 0 hrs. and kept in an airtight container for further use. The remaining moringa oleifera powder was milled for 2.5 hrs., 5 hrs., and 7.5 hrs. respectively in High Energy Ball Milling Equipment. The XRD studies showed that the crystallites size of milled moringa oleifera powder was between 1 nm and 100 nm. The present study reveals surface morphology and crystal structure alteration due to different milling times. The TEM studies showed that the milled nano powder is below 50 nm. UV–vis measurement shows that maximum absorbance for all four samples (MS 0 hr., MS 2.5 hr., MS 5 hr. & MS 7.5 hr.) was nearly identical at 400 nm and slightly lower at 270 nm and substantial absorption at about 650 nm within the visible spectrum, which could be attributed to the fact that there is the presence of protein and cellulose content in the samples. There was a considerable change in wavenumber but no change in the functional group was witnessed in FTIR at different milling times. A biomedical assay was also studied to check the cell viability and cytotoxicity. The test used was MTT Assay; it is a colorimetric assay that is routinely employed in the fields of bio-medical science and biotechnology. It is the conversion of yellow-coloured tetrazolium salt to purple-coloured formazan using NADPH present inside the cell. The results indicated that cell viability also increases by increasing the milling hours. A dosage of 25 µg/ml seems to be optimal for maintaining cell viability. The present research opens a new window in the field of food science & Agriculture that superfine nanoscale powder as a new functional material for its various uses in Biomedical engineering, Food, Health and related sector.